Probiotic-Containing Nanofiber-Based Dental Floss Suppresses Subgingival Red Complex Periopathogens: A Randomized Double-Blind Crossover Trial - Filip Hromcik; Pavla Holochova; Jan Bohm; Eva Kuzelova Kostakova; Zdenek Pokorny; Filip Ruzicka; Petra Borilova Linhartova (Probiotics and Antimicrobial Proteins, 2026)
Recently, a dental nanofloss containing a probiotic ( Ligilactobacillus salivarius ; LS -nanofloss) was developed by our team. This study aimed to evaluate: (i) its impact on subgingival plaque accumulation and gingival bleeding, and (ii) retention of selected subgingival periopathogens and the introduced probiotic bacteria, and (iii) its effect on the quantity of red complex periopathogens in the subgingival environment. This randomized, double-blind, crossover trial was conducted in 30 healthy male participants. Each subject underwent professional flossing and subsequently used LS -nanofloss/probiotic-free (control) nanofloss at two separate 14-day periods, always followed by a 14-day wash-out. Clinical assessments (subgingival plaque accumulation and gingival bleeding) were performed at five time points; subgingival plaque samples were collected at seven time points for quantitative analysis of total bacterial DNA, L. salivarius , a cariogenic bacterium Streptococcus mutans , and red complex periopathogens. Both nanofloss types significantly reduced plaque accumulation and gingival bleeding after 14 days ( p < 0.05), especially in the anterior regions; these improvements, however, regressed after the wash-out period. L. salivarius DNA was detected in 93.3% of samples after professional flossing, 36.7% after self-flossing, and 13.3% even after the wash-out period. The use of LS -nanofloss was associated with a significant reduction in red complex periopathogens ( p < 0.05). The investigated L. salivarius -containing nanofloss proved to be an effective oral hygiene device for subgingival introduction of this probiotic strain. Its application reduced the relative quantity of red complex periopathogens in the subgingival environment, showing potential to prevent the development of periodontitis. The trial was registered retrospectively on 2/9/2025 as NCT07149493.